PROGNOSTIC ASPECT OF MOTORIC MANIFESTATIONS AND MORPHOLOGIC FEATURES REGARDING THE LONG JUMP - Kemal Idrizović; Emir Pašalić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Demand to be acquainted with principles of relations between morphologic features and motoric manifestations, is especially pronounced since motoric ability can be manifested only through what characterizes morphologic structure of the entity. The refore, efficiency of motoric manifestations depends directly on anthropometrical dimensions, as indicated by results of numerous hitherto researches. Conditionality of the realization or achievement of some motoric act, by anthropometrical status characteristics and as reasonable, motoric status itself, makes the basis of this paper.